CULTURAL HEGEMONY AND MEDIA FRAMING: A CRITICAL DISCOURSE ANALYSIS OF POLITICAL NARRATIVES - Abdul Rahman (Penelitian dan Pengembangan Ilmu, 2025)
In the contemporary political landscape, mass media has evolved from a mere information channel into a strategic instrument for the production of cultural hegemony. This study aims to comprehensively review the discursive strategies used by the media to naturalize political narratives into collective